Electrocardiogram interpretation skills in pediatric residents - Crocetti Michael; Thompson Reid (Wolters Kluwer Medknow Publications, 2010)
Objective : The primary objective of this study was to evaluate pediatric residents′ ability to correctly identify electrocardiogram (ECG) findings and pair them to a corresponding cardiac diagnosis. Methods: Forty-six pediatric residents from the Johns Hopkins Children′s Center were surveyed to evaluate their ability to interpret ECGs and factors affecting that ability. Included in the survey was a packet of 10 patient vignettes each accompanied by a 12-lead ECG. The primary outcome variable was the resident′s score of correctly paired ECG findings with the appropriate cardiac diagnosis. One point was given for each pair correctly identified for a maximum of 10 points. Simple and multiple linear regression was used to estimate the magnitude and significance of any association between score of correct responses and resident year, completion of a pediatric cardiology rotation, self-rated ability to read ECGs, and training received in reading ECGs. Results : The mean number of correct ECG findings and cardiac diagnosis pairings out of 10 for the PGY 1 group was 4.1 ± 3, PGY 2 group 4.9 ± 2.9, PGY 3 group 6.6 ± 2, and the PGY 4 group 6.8 ± 1.7. In the unadjusted linear regression model, the PGY 3 group correctly identified 2.4 more pairings compared to the PGY 1 group (P =0.02). Those who completed a pediatric cardiology rotation correctly identified 2.5 more pairings compared to those who did not complete a rotation (P=0.001). Conclusions: ECG interpretation significantly improved from PGY 1 to PGY 3. Educational programs involving ECG interpretation should target those diagnoses with high clinical severity and average to poor resident knowledge.